THE CORRELATION BETWEEN READING COMPREHENSION AND TRANSLATION ABILITY: A Correlational Study on Fourth Year Students at English Department of UNP - Elsa Fadica Rahemi; Jufri Jufri; Havid Ardi (Journal of English Language Teaching, 2013)
Abstract The purpose of this research was to reveal the correlation between reading comprehension and translation ability of fourth year students in English department of UNP. The population and samples of this research was the fourth year students who took translation subject in the seventh semester of academic year 2012 in English Department of UNP. The instrument of this research was a reading comprehension test and translation test. The result of this research showed that the r-calculated (0,677) > r-table (0,355). The hypothesis was tested by using t-test formula and found that t-observed (4,952) > t-table (1,699) with df= n-2 (29) in the level of significance 0,05. In short, the research hypothesis which stated that there was a significant correlation between students’ Reading Comprehension and their Translation Ability was accepted. Kata kunci : Correlation, Translation, Translation ability, Reading Comprehension